2020
DOI: 10.17711/sm.0185-3325.2020.024
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between executive functions and impulsive behavior in adolescents: Comparative study

Abstract: Introduction: Impulsivity can be directly related to maladaptive and disruptive behaviors; specifically, during adolescence, impulsivity is associated with behavioral and social problems, and it has been found that some behavioral difficulties are related to neuropsychological dysfunction of the prefrontal cortex, which is responsible for regulating impulse control and executive functions. Objective. To compare the relationships among executive functions, particularly inhibitory control, behavioral planning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Los resultados de estos trabajos son acordes con los encontrados en la presente muestra. Las características de la impulsividad, identificadas como las acciones poco planificadas, los déficits en la inhibición y en la regulación y control emocional parecen ser manifestaciones de deficiencias observadas también en la disfunción ejecutiva, y aunque los resultados cuando se evalúan los procesos cognitivos asociados a las FEs de forma aislada en ambientes controlados, son contradictorios (Lijffijt, et al, 2004;Panwar et al, 2014;Quintero-Reynaga et al, 2020), parece que la evaluación de las conductas en ambientes ecológicos es fiable. En relación con esto, es importante destacar que es posible que las personas con impulsividad a niveles subclínicos tengan deficiencias en organizar la conducta cuando requieren del uso de múltiples procesos cognitivos de forma simultánea.…”
Section: Discussionunclassified
“…Los resultados de estos trabajos son acordes con los encontrados en la presente muestra. Las características de la impulsividad, identificadas como las acciones poco planificadas, los déficits en la inhibición y en la regulación y control emocional parecen ser manifestaciones de deficiencias observadas también en la disfunción ejecutiva, y aunque los resultados cuando se evalúan los procesos cognitivos asociados a las FEs de forma aislada en ambientes controlados, son contradictorios (Lijffijt, et al, 2004;Panwar et al, 2014;Quintero-Reynaga et al, 2020), parece que la evaluación de las conductas en ambientes ecológicos es fiable. En relación con esto, es importante destacar que es posible que las personas con impulsividad a niveles subclínicos tengan deficiencias en organizar la conducta cuando requieren del uso de múltiples procesos cognitivos de forma simultánea.…”
Section: Discussionunclassified
“…It is worth noting that several studies have shown statistically significant negative relationship between impulsivity, and executive functions (including attentional control), and impulsivity is correlated to executive functions defects and impairment (for example, Foroozandeh, 2017;Hayashi et al, 2017;Quintero Reynaga et al, 2020).…”
Section: Impulsivitymentioning
confidence: 99%